Participation and Organizational Commitment in the Mondragon Group - Rodríguez-Oramas, Alfonso; Burgues-Freitas, Ana; Joanpere, Mar; Flecha, Ramón (Frontiers in Psychology, 2022)
The scientific literature has shown Mondragon Corporation, with 65 years of history, as a clear example that cooperativism can be highly competitive in the capitalist market while being highly egalitarian and democratic. This cooperative group has focused on its corporate values of cooperation, participation, social responsibility, and innovation. Previous scientific research reports its enormous transformative and emancipatory potential. However, studies on the effects of various types of worker participation on competitiveness and workers' psychological wellbeing in this cooperative group exist to a lesser extent. Specifically,, one aspect that needs further empirical research and that represents a competitive advantage for Mondragon is the degree of commitment and emotional attachment that can be observed in the people who work there. For this reason, this paper aims to identify key elements of the democratic participation of workers in these cooperatives that relate to the development of organizational commitment. Based on a communicative and qualitative approach, data collection included 29 interviews to different profiles of workers (senior and junior workers, members and non-members of the cooperative, and researchers involved in the cooperatives) from eight different cooperatives of the Corporation. Through this research methodology, the participants interpret their reality through egalitarian and intersubjective dialogue because their voices are considered essential to measure the social impact. This study found three different ways in which the democratic participation of worker-members in management and ownership contributes to developing affective organizational commitment among those working in Mondragon cooperatives, generating positive psychological and economic outcomes for both workers and cooperatives.